Komunikasi Interpersonal antara Pimpinan dan Karyawan dalam Membangun Hubungan Kerja yang Harmonis pada Perusahaan Bozcilix Clothing Production - Imron, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
This research aims to explain how interpersonal communication is carried out to build harmonious working relationships at the Bozcilix Clothing production company. The problem formulation in this research is how interpersonal communication is carried out to build harmonious working relationships in the Bozcilix Clothing production company. The theory used in this research is interpersonal communication theory which explains how to communicate directly between two people face to face where they exchange messages spontaneously and directly, both through words and body movements. The research method used is a qualitative descriptive method. Data was collected through interviews with leaders and employees as well as analysis of documents related to the company's internal communications. Data analysis is carried out by reducing data, presenting data, and drawing conclusions to find out answers about what is being studied. The results of this research show that the interpersonal communication process carried out by the Bozcilix Clothing Production company uses primary, secondary communication patterns, and uses a transactional communication model which aims to build harmonious working relationships in the Bozcilix Clothing Production company. Researchers found that there were obstacles to interpersonal communication in this research, including differences in perception, errors in conveying messages, delays in response and lack of clarity in the information conveyed.. Keywords: Interpersonal Communication, Primary Pattern, Secondary Pattern, Transactional Model